SYNCHRONIZATION BASED ON GLOBAL STATES AS A GENERAL CONTROL METHOD IN PARALLEL PROGRAMS - Borkowski, J.; Tudruj, M.; Kopanski, D. (International Journal of Computing, 2014)
New parallel program synchronization mechanisms are presented. A specialized synchronizer process, or a hierarchy of such processes, gather information about process states and construct Strongly Consistent Global States, using time interval timestamps. Global predicates evaluated by synchronizers can cause synchronization signals to be sent to processes, the signals trigger asynchronous computation activation or cancellation. The proposed framework is integrated with a message passing system - it is added to the GRADE graphical parallel programming environment to enhance its message-passing based features. Architecture and implementation of the enhancement are discussed.